Evaluation of the vibration state and determination of the stress-strain state of the trash-rack structure of the hydroelectric power plants - A. S. Antonov; N. P. Karablin; K. Ju. Baud; I. V. Baklykov (Vestnik MGSU)
Introduction. The study presents an approach for detecting and identifying the causes of damage to individual key elements of metal structures of the hydroelectric power plant’s trash-rack structure under anthropogenic dynamic impacts. Strength and hydraulic calculations were performed, as well as modal analysis of the structure. The approach is determined and instrumental measurements of actual dynamic characteristics of the trash-rack structure at different pressures are carried out.Materials and methods. A methodology consisting of two blocks was developed to perform measurements of dynamic anthropogenic impacts. The first block is an instrumental and visual inspection to determine the compliance of structures with design solutions, as well as to identify characteristic defects of the trash-rack structure. The measurement of natural frequencies of vibrations and vibration accelerations of structures at different pressures was carried out using piezoelectric vibration transducers AR90, the measurement of vibration accelerations by seismic receivers A16 and the receiving station MIC-200. The second block is mathematical modelling. The hydraulic regime and the stress-strain state were specified, frequencies and forms of natural vibrations of the structure were determined. Computational studies were carried out in the universal industrial software complex ANSYS Mechanical and ANSYS CFX.Results. The survey revealed the presence of systematically occurring cracks in the load-bearing frame, the mismatch of the position of the struts to the design. Hydrodynamic loads are specified, diameter and frequency of vortex formation are determined. The stresses in the metal struts do not exceed the standard values for the steel used. The performed direct measurement of vibration of structural elements demonstrated that the most dangerous frequency range is 40.30–41.75 Hz.Conclusions. It is revealed that the main cause of damage to the trash-rack structure is the displacement of forced frequencies and the shape of natural oscillations to the zone of operation of hydraulic units, which led to the concentration of stresses at the ends of the struts in the zone adjacent to the gussets. The junction of struts to the gusset had insufficient length, which led to the transfer of stresses to the edge of the gusset and, as a result, to the concentration of stresses and the formation of cracks in the direction of the main stresses in the node.